Salang Pinjam: Maintaining Traditional Pawn Practice against the Practice Regulated by Divide et Impera Politics - Gusril Basir; Fajrul Wadi; Busyro Busyro; Rahmiati Rahmiati; Adlan Sanur Tarihoran (Khazanah Sosial, 2023)
Salang pinjam had been carried out by many Minangkabaunese before the arrival of the Dutch colonialists. The presence of the Dutch colonialists shifted the tradition of salang pinjam into pagang gadai (pawn) as part of the Devide et Impera politics which aimed at breaking up the unity of Minangkabau people. The transition from the concept of salang pinjam to gadai (pawning), apart from not being in accordance with Islamic teachings, also often causes disputes in the communities. Even so, in several Minangkabau areas the tradition of salang pinajm still survives to ensure the continuity of religious-based customs, including in Paninjauan Village, Tanah Datar regency. This study was conducted to describe the concept of salang pinjam and how it differs from the Dutch version of pawning. This research is field research with the data sources obtained from Paninjauan Village’s community leaders and parties who have carried out salang pinjam. The data were collected through direct interviews with informants, then classified according to the questioned-themes. Then, the data were analyzed descriptively. This study concluded that the essence of salang pinjam is borrowing from each other, one party borrows money or gold and the other party borrows land or rice fields. Based on Islamic teachings, this transaction does not violate Islamic rules and will not cause any disputes. This is different from pawnshops regulated by the Dutch Colonial by which borrowing money must be accompanied by collateral in the form of land, and this way becomes a source of problems for two reasons; first, it is contrary to Islamic teachings because it utilizes collateral assets; and second, the collateral must be returned to the borrower after seven years without compensation, and in reality the community is not willing to just return it unless the borrowers must return the money they have borrowed.